A review on the state-of-the-art advances for CO2 electro-chemical reduction using metal complex molecular catalysts - Louis, Hitler; Akakuru, Ozioma Udochukwu; Monday, Philip; Funmilayo, Oyebanji Oluwatomisin (Eclética Química, 2019)
Significantly, global warming which is caused by CO2 emission and energy shortage are global problems resulting from artificial photosynthesis because it required many functions (light harvesting, Z water, and oxidation scheme). Therefore, photocatalytic systems development for CO2 reduction is germane in this field. Metal complexes molecular catalyst have become prevalent homogeneous catalysts for carbon dioxide (CO2) photocatalytic reduction since it was initially known as CO2 reduction catalysts in the 70s and the 80s, while utmost part involved macrocyclic cobalt(II) and nickel(II) complexes. This review article presents a broad understanding on some active catalysts recently reported as a metal complex molecular catalytic schemes for CO2 reduction, alongside catalytic activity, stability, selectivity under electro-reduction, and photoreduction circumstances. The progress of in situ spectroelectrochemical methods, typically supported via theoretical calculations, helped to access this know-how by providing information which enabled researchers to acquire more in-depth perception into unveiling the catalytic reaction and mechanisms intermediates.